2018
DOI: 10.1177/0886260518781806
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Prevalence of Elder Abuse in Brazil

Abstract: We aimed to assess the prevalence and characterize the profile of elder abuse in Brazil in this quantitative descriptive and exploratory study using a document analysis of cases of elder abuse against people aged 60 and over reported to Brazil's Notifiable Disease Information System ( Sistema de Informação de Agravos de Notificação-SINAN) from 2009 to 2013. Association between age groups (older adults and non-older adults) and (a) characteristics of the victims (gender, age, and race), (b) characteristics of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
1
12
0
7
Order By: Relevance
“…It is estimated that of the 901 million people over 60 years old, 15% were victims of some form of abuse; and it is suggested that this number may be higher since such crimes are underreported. [37][38] Situations of social vulnerability cause dignity to be violated and it is important to create mechanisms to guarantee what the Universal Declaration of Human Rights stipulates, ensuring that dignity is "protected". 39 The relationship between social vulnerability, violence and dignity observed in the present study did not occur in the canadian study, and this difference can be explained by the brazilian political and social situation, which appears in the speech of many participants of this study associated with the perception of dignity.…”
Section: /15mentioning
confidence: 99%
“…It is estimated that of the 901 million people over 60 years old, 15% were victims of some form of abuse; and it is suggested that this number may be higher since such crimes are underreported. [37][38] Situations of social vulnerability cause dignity to be violated and it is important to create mechanisms to guarantee what the Universal Declaration of Human Rights stipulates, ensuring that dignity is "protected". 39 The relationship between social vulnerability, violence and dignity observed in the present study did not occur in the canadian study, and this difference can be explained by the brazilian political and social situation, which appears in the speech of many participants of this study associated with the perception of dignity.…”
Section: /15mentioning
confidence: 99%
“…Quanto aos dados sobre mortalidade, obtiveram-se os dados do SIM a partir da mesma fonte que o SINAN-Net, e as causas básicas dos óbitos estão agrupadas de acordo com a classificação proposta no CID-10 (Código Internacional de Doenças): acidentes de transporte (V01-V99); outras causas externas de lesões acidentais (W00-X59); lesões autoprovocadas voluntariamente (X60-X84); agressões (X85-Y09); eventos cuja intenção é indeterminada (Y10-Y34); complicações de assistência médica e cirúrgica (Y40-Y84) e sequelas causas externas de morbidade e mortalidade (Y85-Y89) (11) . Buscou-se, também, a caracterização dos óbitos segundo as variáveis disponíveis: sexo, faixa etária, raça/cor, estado civil, local de ocorrência e causa do óbito (18) .…”
Section: Métodosunclassified
“…A violência impacta a qualidade de vida dos idosos, podendo ter graves efeitos e resultando em problemas psicológicos, financeiros, sociais e físicos, e na incapacidade perene, permanente ou a morte da pessoa idosa (11) . A incapacidade pode, por sua vez, aumentar a dependência funcional do idoso, aumentando o risco da violência física e de outros tipos de abuso por terceiro (12) .…”
Section: Introductionunclassified
See 2 more Smart Citations